2004
DOI: 10.1007/s10350-004-0688-7
|View full text |Cite
|
Sign up to set email alerts
|

Large Bowel Obstruction: Predictive Factors for Postoperative Mortality

Abstract: Large bowel obstruction still has a high of mortality rate. An accurate preoperative evaluation of severity factors might allow stratification of patients in terms of their mortality risk and help in the decision-making process for treatment. Such an evaluation would also enable better comparison between studies performed by different authors. Principles and stratification similar to those of distal lesions should be considered in patients with proximal colonic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
5
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 25 publications
9
134
5
11
Order By: Relevance
“…18 More recently, Biondo and coworkers have reported that preoperative renal failure, as evidenced by an elevated serum creatinine concentration alone, was a more signi¢cant independent predictor of 30-day mortality than ASA grade. 19 It is therefore of interest that in the present study, preoperative serum urea, both preoperatively and day one postoperatively, was superior to creatinine in predicting 30-day mortality. Further prospective studies are required to con¢rm that serum urea has prognostic value independent of ASA grade.…”
Section: Discussionmentioning
confidence: 63%
“…18 More recently, Biondo and coworkers have reported that preoperative renal failure, as evidenced by an elevated serum creatinine concentration alone, was a more signi¢cant independent predictor of 30-day mortality than ASA grade. 19 It is therefore of interest that in the present study, preoperative serum urea, both preoperatively and day one postoperatively, was superior to creatinine in predicting 30-day mortality. Further prospective studies are required to con¢rm that serum urea has prognostic value independent of ASA grade.…”
Section: Discussionmentioning
confidence: 63%
“…It is also well known that emergency surgical treatment of colorectal obstruction deals with a high morbidity and mortality on the range of 46% and 19% respectively. [18][19][20] Results from the surgical group in the series are in that context.…”
Section: Discussionmentioning
confidence: 99%
“…In patients in whom the risk of surgery is higher than average (for example American Association of Anesthesiologists classification [ASA] III, or age > 70 years), 50,51 SEMS as a bridge to elective surgery may still be appropriate management. 15 It can convert an emergency into an elective operation and provide time for preoperative optimization of comorbidities and improvement in physiology.…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%